The Foundations of Russian Statehood: The Pentabasis, National History, and Civic Values in Wartime Russia - Kortukov, Dima; Waller, Julian G (Communist and post-communist studies, 2025)
The content of Russian educational material on moral-cultural issues has gradually shifted over the Putin tenure toward a standard that emphasizes state patriotism, syncretic pride in the achievements and heroes of the Tsarist, Soviet, and post-Soviet periods, and traditional sociocultural values, including respect for religious authorities. The onset of the 2022 Russo-Ukrainian War has caused a shift in debates over national pedagogic inculturation among domestic Russian elites, with many calling for the return of “ideology” to properly ensure the formation of future, regime-loyal generations. This article analyzes the first official document of the wartime period that deals with questions of Russia’s ideology—the educational curriculum guidance packet titled “Foundations of Russian Statehood” (FORS) and promoted by the Presidential Administration for use in Russian universities. The article typifies the state of pre-war Russian moral-cultural pedagogical material within its shifting, illiberal ideological context, compares this pre-war setting with the FORS document and the concomitant discursive shift among key Russian officials, and provides a descriptive analysis of FORS itself. In doing so, the article identifies the evocative “pentabasis” framework of the FORS document as a potential core of a crystallizing, official ideology in modern wartime Russia.